2022
DOI: 10.1007/s00477-022-02218-x
|View full text |Cite
|
Sign up to set email alerts
|

A new picking algorithm based on the variance piecewise constant models

Abstract: In this paper, we propose a novel picking algorithm for the automatic P- and S-waves onset time determination. Our algorithm is based on the variance piecewise constant models of the earthquake waveforms. The effectiveness and robustness of our picking algorithm are tested both on synthetic seismograms and real data. We simulate seismic events with different magnitudes (between 2 and 5) recorded at different epicentral distances (between 10 and 250 km). For the application to real data, we analyse waveforms fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The multivariate version of the picking algorithm from [17] was tested through simulations. With this aim, we simulated waveforms with different magnitudes and distances from the nearest seismic station.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The multivariate version of the picking algorithm from [17] was tested through simulations. With this aim, we simulated waveforms with different magnitudes and distances from the nearest seismic station.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a further advantage of the multivariate algorithm with respect to its univariate counterpart. Indeed, the preliminary experiments in [16] showed that the univariate algorithm achieved the best performance with decreasing distances (from the nearest seismic station that recorded the event) and with increasing magnitude. NAs occurred often when the distance is large and the magnitude was small, indicating scenarios in which the P-and S-waves were basically indiscernible from the noise.…”
Section: Simulation Study: Multivariate Sequence Waveformsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, several applied case studies highlight the potential of spatiotemporal data science in giving reliable solutions to real-world problems. Papers in this issue include case studies from hydrology and hydromorphology (Budiman et al 2021;Wang et al 2021;Rolim et al 2021;Tang et al 2021;Tian et al 2021;Sottile et al 2021;Han and Morrison 2021), to geology (Giaccone et al 2021), geomechanics (Li et al 2021;Luo et al 2021;Lombardo and Tanyas 2021;Aguilera et al 2022;D'Angelo et al 2022;Bryce et al 2022;Grimm et al 2022), atmospheric phenomena and renewable energy (La Fata et al 2022;Amato et al 2022;Kajbaf et al 2022), pathogenic viruses and associated diseases (Niraula et al 2022;Temple et al 2022).…”
Section: Introductionmentioning
confidence: 99%